Application of Motivation in Arab EFL/ESP Learners’ Settings: A Socio-Cultural Approach - Benahnia, Abdellah (European Scientific Journal, ESJ, 2017)
One of the most challenging aspects of language teaching that faces teachers in general and those in the Gulf area in particular is how to "motivate" their learners. Unlike in any other parts of the world, a large segment of the student population in the Gulf area come either from a middle-class or a wealthy-class. However, the poor-class category seems to get larger any time there is a recession period or a drop in the price of oil. Therefore, the student population can be categorized into two main streams: those who are considering education as a vehicle that helps a person to achieve his goals and objectives and excel in life; and another category that looks at education as supplementary luxury added to their lavish life-style and accumulated wealth by their families. This itself serves as a sociocultural barrier to the application of motivation in class in addition to other barriers. This article tries to shed light on some of those barriers and provide suggestions and recommendations on how to boost the learners’ motivation, and help reducing underachievement and failures in second language learning in the Gulf area.